A Reference Architecture for Virtual Human Integration in the Metaverse: Enhancing the Galleries, Libraries, Archives, and Museums (GLAM) Sector with AI-Driven Experiences - Orestis Spyrou; William Hurst; Caspar Krampe (Future Internet)
The digital transformation of the GLAM (galleries, libraries, archives, and museums) sector is a multifaceted process that must address a range of requirements and critical challenges, such as traceability, long-term preservation, and sustainability. The potential of disruptive technologies to revolutionize this sector is significant, offering new ways to overcome these challenges and align with the broader objectives of smart cities. While substantial research has been conducted on the digital transformation of the GLAM sector, many opportunities remain unexplored by various stakeholders. This paper contributes to the field by proposing a reference architecture rooted in a design-oriented approach for developing and implementing processes related to the digital transformation within the context of smart cities. To illustrate the practical application of the proposed architecture, a proof of concept was developed in the form of an immersive digital gallery, which features an AI-powered virtual storyteller. The gallery, built using the open, cross-platform, Unreal, incorporates digitized physical art and a virtual metahuman tutor who guides users through the gallery. This interactive 3D environment enables users to explore the space, engage with artworks, and interact with a virtual guide. The environment’s performance was evaluated using a keystroke-level model analysis. Key findings from a pilot study involving 10 users showed that, when directed by the AI storyteller, the average time to locate an artwork was 16.5 s, while the average time to ask a question was 15.8 s. By integrating such technologies, the GLAM sector can contribute to the cultural fabric of smart cities, fostering more sustainable, accessible, and interactive public spaces.